Debunking two myths of the weekend effect - Foong Soon Cheong (International Journal of Financial Studies, 2016)
This paper finds the weekend effect to be a remarkably robust anomaly and refutes the widespread belief that the weekend effect is due to data-mining or a consequence of some unusual/rare events. Out-of-sample analysis finds both the mean and median return on Monday is lower than that on Friday in nearly all years. It also reconciles and explains how some prior studies reached such an erroneous conclusion.
Keywords: G12; G14; 330; Weekend effect; Monday effect; anomaly; data-mining